(untitled) (AYUSHDHARA, 2018)
In Ayurvedic texts, diseases of the female reproductive system have been collectively described as Yoni Vyapada. Udavarta Yoni Vyapada is one in which the woman feels pain and distress in the peri-menstrual period along with systemic symptoms. It is an extremely common disease affecting majority of women even in present day world. It is caused by vitiation of Vayu. According to the clinical features, Udavarta Yoni Vyapada can be correlated with primary dysmenorrhoea. Chaturbeeja Churna is mentioned in Bhava Prakasha Nighantu, as Vata shamaka. Yogic practices regulate body mechanism and improve the psychology of the patients. In the present study, 50 patients were studied. The results have been presented after taking into account every aspect of the history of the patient. Then thorough examination was done. After that all the symptoms were observed in these patients during the trial for improvement. These patients were treated in single group. Patients were treated with Chaturbeeja churna with yogic practices. Chaturbeeja Churna 3g bd with hot water along with specific Yogic Practices for 3 menstrual cycle. 26 patients were markedly improved, 15 moderately improved and 9 patients were improved. From the above discussion, we can say that therapy (Chaturbeeja Churna and Yogic with practices) had statistically highly significant results and was very effective.